2013
DOI: 10.1016/j.scriptamat.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal effect on densification kinetics during microwave sintering of α-alumina

Abstract: The microstructural evolution and densification kinetics of a-alumina were investigated and compared between conventional sintering and microwave sintering at 2.45 GHz in the intermediate stage, where the microwave seems to be the most efficient. Based on classical kinetics models, the calculated kinetics parameter demonstrated that the densification is greatly influenced by the presence of an electromagnetic field during sintering. It was assumed that the grain boundary diffusion is enhanced by an electromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…These results clearly demonstrate that microwaves enhance the densification of alumina compacts during the initial and intermediate stages of sintering, which was also evidenced by Zuo et al [23] in a multimode cavity furnace. This effect was not observed in hybrid microwave sintering in our experiments.…”
Section: Resultssupporting
confidence: 84%
“…These results clearly demonstrate that microwaves enhance the densification of alumina compacts during the initial and intermediate stages of sintering, which was also evidenced by Zuo et al [23] in a multimode cavity furnace. This effect was not observed in hybrid microwave sintering in our experiments.…”
Section: Resultssupporting
confidence: 84%
“…Many authors reported an acceleration of the sintering kinetics in microwave compared to conventionally sintered samples [38][39][40][41][42] for the same thermal cycle. The origin of this so-called "non-thermal effect" or "microwave effect" is still debated but a possible explanation can be the action of ponderomotive forces at the pore/grain boundary junctions [43][44][45][46][47] and/or diffusion mechanism enhancements induced by the microwave alternative fields.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave field can enhance the atom kinetic energy and a high-frequency electric field can promote the migration of the charged vacancy at the grain surface, which decrease the sintering activation energy are enhance the sintering process [15][16]. Microwaves could exert a ponderomotive force for mass transport in ceramics [17], as well as, microwave provides an electromagnetic pressure, which is similar with the applied pressure in hot pressing sintering, to the powder compact, resulting in an additional driving force for densification [18].…”
Section: Introductionmentioning
confidence: 99%